Mental Health in the Classroom (Journal of Parents and Teachers, 2023)
The Education Community and families seem everytime more surprised about the increasing number of teenagers that show highly mental suffering, who must receive specialised treatment. We go through the most common disorders found in secundary school and in the last years of elementary school.
Keywords: anguish; anxiety; personality traits; relaxation; student's attitude